Latvia’s Ambiguous Attitude towards the Framework Convention for the Protection of National Minorities: Is Diversity a Threat? - Kascian, Kiryl (Public Governance, Administration and Finances Law Review, 2024)
On 22 February 2024, the Advisory Committee on the Framework Convention for the Protection of National Minorities published a critical opinion on Latvia within the framework of the fourth monitoring cycle. This text is centred on government comments as an important element of the standardised FCNM monitoring mechanisms provided by the Latvian Government during the four monitoring circles. This study identifies and assesses the key arguments and techniques employed by Latvia in this sectoral dialogue framework. It shows that the Latvian authorities view diversity as a threat to social cohesion, and their endeavours, inter alia, in the minority education domain, combine references to Latvia’s traumatic historical experience, constitutional identity, and the margin of state discretion that camouflage the absence of political will to advance minority rights. Among other negative factors, this signals a dangerous path that could likely be followed by other states that are parties to this Convention.